Le dandysme et la figuration de l’histoire - Ralickas, Eduardo (Ciel variable)

(untitled) (Les Productions Ciel variable, 2004)
Abstract Yinka Shonibare's works can be characterized in terms of their powerful deconstruction of Western notions of identity. In this light, the artist's embrace of the figure of the dandy is decisive, for it signals the complex play of forces underlying the social construction of selfhood. The author argues that dandyism offers Shonibare a historical model upon which to enact his critique of subjectivity. Moreover, dandyism traverses the very logic of Shonibare's practice, thus creating a tension between history and an immanent critique of its categories. The ontology of the figure of the dandy is analyzed in order to stress the reflective nature of its activity. This ultimately grounds Shonibare's simultaneous critique of historical dandyism and the artist's understanding of the self in terms of dandyism's inherent masquerade.